The Liquidity Regulation and Savings Banks' Liquid Assets - Dorothee Holl; Andrea Schertler (Kredit und Kapital, 2010)
The Liquidity Regulation and Savings Banks' Liquid Assets For their short-term payment obligations, savings banks hold substantially more liquid assets than the liquidity regulation requires. This paper investigates whether sight deposits, an important funding source for savings banks, help in explaining liquid asset holdings in excess of regulatory requirements. We analyze whether savings banks transform sight deposits in illiquid assets less intensively than is permitted because (i) the liquidity regulation underestimates actual withdrawal rates (underestimation effect) and/or (ii) savings banks are subject to limits in their lending to non-banks that they do not offset by, for instance, medium-term interbank lending or fixed asset holdings (lending effect). In our sample, we do not find the underestimation effect to be applicable as actual deposit withdrawal rates are in most cases lower than the regulatorily specified rate. However, we find the lending effect to be at work: Savings banks with low shares of loans to non-banks do not transform sight deposits into illiquid assets as intensively as savings banks with high shares of non-bank loans. Our analysis does not only show that liquid assets positively depend on sight deposits, but also shines a light on how bank size and the individual bank's position in the interbank market affect liquid assets. (JEL G21) – – Die Liquiditätsregulierung und liquide Aktiva von Sparkassen Sparkassen verfügen über wesentlich mehr innerhalb des nächsten Monats verfügbare Zahlungsmittel, als sie gemäß Liquiditätsverordnung für ihre in diesem Zeitraum abrufbaren Zahlungsverpflichtungen halten müssen. Die vorliegende Arbeit untersucht, ob Sichteinlagen, die eine wesentliche Finanzierungsquelle für Sparkassen darstellen, zu dem hohen Bestand an Zahlungsmitteln beitragen, weil (i) die regulatorisch spezifizierte Marke der Einlagenabzüge die tatsächlichen Abzüge unterschätzt (Unterschätzungseffekt) und/oder (ii) Sparkassen Grenzen bei der Kreditvergabe an Nicht-Banken ausgesetzt sind, die sie nicht durch Investitionen in andere illiquide Aktiva (z. B. mittelfristige Interbankkredite) kompensieren (Krediteffekt). Wir finden keine Evidenz für einen Unterschätzungseffekt: Der Vergleich der tatsächlichen Einlagenabzüge mit der regulatorisch spezifizierten Marke von 10% deutet an, dass die regulatorische Marke in dem von uns verwendeten Datensatz als konservativ zu bezeichnen ist. Wir finden jedoch Hinweise auf das Wirken eines Krediteffekts: Sparkassen mit wenigen Krediten an Nicht-Banken transformieren Sichteinlagen weniger intensiv in illiquide Aktiva als Sparkassen mit vielen Nicht-Bankkrediten. Unsere Untersuchung zeigt nicht nur, dass die Zahlungsmittel positiv von den Sichteinlagen abhängen, sondern gibt auch Anhaltspunkte, wie bankspezifische Faktoren das Halten von Zahlungsmitteln beeinflussen.
Keywords: G21; 330